Penggunaan Media Interaktif Fraction Splat Untuk Kemampuan Berpikir Numerik Siswa Sekolah Dasar Negeri - Waluyo, Rifda Aini; Fiantika, Feny Rita (SITTAH: Journal of Primary Education, 2024)
Implementing Fraction Splat interactive media has significantly improved the numerical thinking abilities of grade 3 elementary school students in fraction material. This research aims to explore the effectiveness of this media in increasing students' understanding of fractions. The research uses descriptive qualitative data collection through written tests, student response questionnaires, interviews, observation, documentation, and the Miles and Huberman model data analysis techniques. The results showed that students with high abilities (TI) showed good skills in understanding and applying the concept of fractions. Meanwhile, students with moderate abilities (SI) show progress in understanding the concept of fractions but still experience difficulties in several aspects, such as participating in presenting discussion results, asking evaluation questions, and writing summaries or conclusions. Meanwhile, students with low ability (RI) have difficulty identifying and calculating fractions but can apply these concepts in everyday situations. Thus, the results of calculating student response questionnaires from the three subjects, it was found that the three subjects showed that the Fraction Splat interactive media was very effective, especially in helping subjects understand fraction material, and was included in the "Good" category with a percentage of 90% of 88.16% for use. Fraction Splat interactive media.